ANALISIS KEDISIPLINAN SISWA MELALUI KETELADANAN GURU PADA SISWA KELAS IVE SDN 007 SUNGAI PINANG - Margareta (SISTEMA: Jurnal Pendidikan, 2020)
This research was motivated by the analysis of student discipline through teacher's accuracy. The purpose of this study was to find out how students were disciplined through teacher training at SDN 007 Sungai Pinang. The subjects in this study were the principal, the IVE homeroom teacher and the IVE class students. The instruments in this study are the researchers themselves. Data collection techniques used are interviews and documentation. Data analysis conducted in this study there are three stages, namely data reduction, data presentation, and conclusion drawing. Checking the validity of the data used is the triangulation of the source. The results of the research can be concluded that the discipline at SDN 007 Sungai Pinang can be said to be good, with the criteria of coming to school on time, diligently studying in school, obeying school rules and collecting assignments on time as well as the standard shown by teachers including attending school on time, entering learning hours on time, and arranging students who will enter the classroom regularly. In general, the discipline of students through teacher awareness at SDN 007 Sungai Pinang in terms of discipline is good, and the impersonation of examples of teacher's exemplary behavior is also quite good. The modifications made by the students are still in the stage of reviewing each teacher's behavior. Keywords: student discipline, teacher's accuracy Penelitian ini dilatarbelakangi oleh analisis kedisiplinan siswa melalui keteladanan guru. Tujuan dalam penelitian ini ialah untuk mengetahui bagaimana kedisiplinan siswa melalui keteladanan guru di SDN 007 Sungai Pinang. Subjek dalam penelitian ini adalah kepala sekolah, guru wali kelas IVE dan siswa kelas IVE. Instrumen dalam penelitian ini adalah peneliti itu sendiri. Teknik pengumpulan data yang digunakan adalah wawancara dan dokumentasi. Analisis data dilakukan dalam penelitian ini ada tiga tahap yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Pemeriksaan keabsahan data yang digunakan adalah triangulasi sumber. Hasil dari penelitian dapat disimpulkan bahwa kedisiplinan yang ada di SDN 007 Sungai Pinang sudah dapat dikatakan baik, dengan kriteria datang ke sekolah tepat waktu, rajin belajar di sekolah, menaati aturan sekolah dan mengumpulkan tugas tepat waktu serta keteladanan yang ditunjukan guru diantaranya hadir sekolah tepat waktu, masuk jam pembelajaran tepat waktu, dan mengatur siswa dengan yang akan masuk kelas secara teratur. Secara umum kedisiplinan siswa melalui keteladanan guru di SDN 007 Sungai Pinang dalam hal kediplinan sudah termasuk baik, dan peniruan contoh perilaku keteladanan guru juga terbilang baik. Modifikasi yang dilakukan siswa masih dalam tahap merefrensi dari setiap perilaku guru. Kata Kunci : kedisiplinan siswa, keteladanan guru